The Analysis of Library Collection, Electronic Resources, and Librarian Services Quality on The Student’s Satisfaction - Hassan Gorondutse, Abdullahi; Nuhu, Mohammed; Anuar Bin Ishak, Khairol (International Journal of Engineering and Technology, 2018)
The studies on library user satisfaction have become a topic of recent debate. the aimed of this paper is to analyze the effects of library collection, e-resources, and librarian service quality towards student satisfaction in the sultanah bahiyah library of uum. a sample of 80 were employees based on probability sampling technique adopted. the data were obtained from the respondents using a questionnaire.the study used ibm spss statistics 24 application software foranalysis, descriptive analysis, reliability analysis, regression analysis, and hypothesis testing results using. the results and findings shown that the library collection, e-resources, and librarian service quality are significantly related to the student satisfaction in the sulthanah bahiyah library of uum. therefore, the result of this study found that the best services, physically and technically, provided by the sultanah bahiyah libraryhas been satisfying the customers, which are students of universiti utara malaysia generally, and especially the students who visit the library. hence, this paper recommended that sulthanah bahiyah library uum to improve their performance in order to meet the visitorâ€™s satisfaction, especially in the area of quality of librarian services.the future researchers employ other factors besides of library collection, e-resources, and librarian service quality towards the student satisfaction. Â Â Â Â